Mechanisms and Representations of Language-Mediated Visual Attention - Huettig, Falk; Mishra, Ramesh K.; Olivers, Christian N. (Frontiers in Psychology, 2012)
The experimental investigation of language-mediated visual attention is a promising way to study the interaction of the cognitive systems involved in language, vision, attention, and memory. Here we review recent research addressing three key issues with regard to how this oculomotor behavior is instantiated: levels of representation at which language-derived and vision-derived representations are integrated; attentional mechanisms; and types of memory. Central points in our discussion are (a) the possibility that local microcircuitries involving feedforward and feedback loops instantiate a common representational substrate of linguistic and non-linguistic information and attention; and (b) that an explicit working memory may be central to explaining interactions between language and visual attention. We conclude by discussing future directions; in particular the merits of testing distinct, non-student, participant populations.